ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI PADI DI KECAMATAN BATANGHARI KABUPATEN LAMPUNG TIMUR - Dirgantari, Indah Aprilia; Haryono, Dwi; Endaryanto, Teguh (Lampung University, 2024)
This research aims to analyze the income and welfare level of rice farming households. The purposive choice of Batanghari District in East Lampung Regency as the research's location. The survey approach was applied to this research, which was carried out between November 2022 and December 2022. The sample for this research consisted of 54 rice farmers taken using the simple random method. This research employed descriptive quantitative data analysis. The results show that rice farming conducted by rice farmers is financially successful because of the R/C value is 2.37 in the rainy season (MH) and 2.35 in the dry season (MK), indicating that the farm is financially successful and practicable with an R/C value of greater than one. Rice farmer household income consists of several sources of income, rice farm income, non rice income, off farm income, and non farm income with a total average income of IDR 30,813,218.52/year. Farmer household expenditure is for food expenditure of IDR 7,833,004.37/year, while non-food expenditure of IDR 21,314,555.56/year. The results are categorized as sufficient according towelfare level of rice farmer promoted by Sajogyo with a percentage of 70.37%, and included in more prosperous criteria based on Good Serivice Ratio’s welfare level with GSR <1 and the total percentage of 92.59%. Key words : Farm income, household expenditure, household income, rice, welfare